2022
DOI: 10.1364/oe.457593
|View full text |Cite
|
Sign up to set email alerts
|

Robust topological one-way edge states in radius-fluctuated photonic Chern topological insulators

Abstract: Recent developments in topological photonics have shown that the introduction of disorders can yield the innovative and striking transport phenomena. Here, we theoretically investigate topological one-way edge states in radius-fluctuated photonic Chern topological insulators (PCTIs), which are composed of two-dimensional gyromagnetic photonic crystals with cylinder site fixed but with cylinder radius fluctuated. We use a fluctuation index to characterize the degree of radius fluctuation, employ two empirical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The results showed that the gap Chern number of Al 2 O 3 PC was 0, and thus the bandgap was trivial. Conversely, the gap Chern number in the second bandgap (between the second and third bands) of YIG PC was +1(or −1) when the EMF was −H 0 (or +H 0 ), which revealed that this bandgap was topologically nontrivial [54,55]. On the other hand, because the bandgap of Al 2 O 3 PC overlapped the second bandgap of YIG PC, the number of topological one-way edge states in the waveguide composed of these two PCs was equal to the difference of gap Chern numbers, and the propagation direction of topological one-way edge states was determined by the sign of gap Chern numbers.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the gap Chern number of Al 2 O 3 PC was 0, and thus the bandgap was trivial. Conversely, the gap Chern number in the second bandgap (between the second and third bands) of YIG PC was +1(or −1) when the EMF was −H 0 (or +H 0 ), which revealed that this bandgap was topologically nontrivial [54,55]. On the other hand, because the bandgap of Al 2 O 3 PC overlapped the second bandgap of YIG PC, the number of topological one-way edge states in the waveguide composed of these two PCs was equal to the difference of gap Chern numbers, and the propagation direction of topological one-way edge states was determined by the sign of gap Chern numbers.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, as plotted in Figs. 2(e) and 2(f), Yang et al [77] and Chen et al [75] respectively demonstrated that chiral one-way edge states can exist in position-disordered and radius-fluctuated GPCs. The calculation results showed that photonic topological bandgaps are far more sensitive to disorders with a radius fluctuation than with a position randomness.…”
Section: Chiral Topological Photonic Statesmentioning
confidence: 98%
“…Additionally, it should be noted that the perturbation of the external magnetic field strength had almost no influence on the transport behavior of the one-way edge states (see more detailed calculations in the Supplemental Information ). Moreover, Chen et al also demonstrated that the realization of the one-way edge states in a GPC system has a very strong tolerance to the nonuniform magnetization [ 40 ].…”
Section: Topological Resistance-free One-way Transportmentioning
confidence: 99%